Resilience policing and climate change: adaptive responses to crises and emergencies - Mutongwizo, Tariro (Routledge international handbook of policing crises and emergencies, 2025)
This chapter sets out to consider the role of police when it comes to managing the human security impacts of acute natural disaster events which are expected to occur more frequently due to climate change. To this effect, it sets out to conceptualise traditional governmental policing actors as part of wider emergency management webs which work to promote resilience in anticipation of, and in response to, these crises. Noting the relative scarcity of empirical research on policing during natural disasters, we examine this phenomenon in relation to two key examples (Hurricane Katrina and Hurricane Harvey) which illustrate the need for traditional policing actors to develop capabilities which enable them to anticipate and respond to non-traditional security threats. This was particularly evident during Hurricane Katrina, where marginalised communities found themselves ‘over-policed and under-protected’ by a combination of public and private policing actors. Years later, the police response to Hurricane Harvey illustrates that even relatively well-prepared police organisations which have taken significant steps to improve their adaptive capabilities may continue to rely on traditional policing mentalities and activities which are of questionable utility when it comes to promoting community safety in the context of environmental crises. Accordingly, the chapter concludes by examining a framework for ‘resilience policing’ proposed by Mutongwizo et al. (2021) and considers its potential utility and limitations for enhancing the governance and delivery of security in anticipation of the growing frequency and severity of natural disaster events.